The Emergence of Value-Based Leadership Behavior at the Frontline of Management: A Role Theory Perspective and Future Research Agenda - Chang, Sin Mun; Budhwar, Pawan; Crawshaw, Jonathan (Frontiers in Psychology, 2021)
The importance of value-based leadership such as authentic, ethical and servant leadership is inconspicuous. However, the benefits of these leadership approaches are often only explained through the behaviour of their followers. As such, limited research has communicated the leader’s motivation for pursuing such leadership behaviour, resulting in such discourse to escape theorizing. We draw upon role theory and paid attention to the role of higher-level management (leadership) through the trickle-down model to underline their importance in the organisation. We then expand this role theory framework by synthesising research to explain the emergence of value-based leadership behaviour at the frontline of management. In doing so, we aim to provide a stronger explanation of the emergence of value-based leadership in organisations. We conclude this analysis by guiding future research in the form of propositions to investigate the psychological process and organisational factors to empirically examine the proposed role framework.